DNA Repair Gene Patterns as Prognostic and Predictive Factors in Molecular Breast Cancer Subtypes. (25th September 2013) - Santarpia, Libero; Iwamoto, Takayuki; Di Leo, Angelo; Hayashi, Naoki; Bottai, Giulia; Stampfer, Martha; André, Fabrice; Turner, Nicholas C.; Symmans, W. Fraser; Hortobágyi, Gabriel N.; Pusztai, Lajos; Bianchini, Giampaolo
Abstract : DNA repair pathways can enable tumor cells to survive DNA damage induced by chemotherapy and thus provide prognostic and/or predictive value. We evaluated Affymetrix gene expression profiles for 145 DNA repair genes in untreated breast cancer (BC) patients ( n = 684) and BC patients treated with regimens containing neoadjuvant taxane/anthracycline ( n = 294) or anthracycline ( n = 210). We independently assessed estrogen receptor (ER)‐positive/HER2‐negative, HER2‐positive, and ER‐negative/HER2‐negative subgroups for differential expression, bimodal distribution, and the prognostic and predictive value of DNA repair gene expression. Twenty‐two genes were consistently overexpressed in ER‐negative tumors, and five genes were overexpressed in ER‐positive tumors, but no differences in expression were associated with HER2 status. In ER‐positive/HER2‐negative tumors, the expression of nine genes ( BUB1, FANCI, MNAT1, PARP2, PCNA, POLQ, RPA3, TOP2A, and UBE2V2 ) was associated with poor prognosis, and the expression of one gene ( ATM ) was associated with good prognosis. Furthermore, the prognostic value of specific genes did not correlate with proliferation. A few genes were associated with chemotherapy response in BC subtypes and treatment‐specific manner. In ER‐negative/HER2‐negative tumors, the MSH2, MSH6, and FAN1 (previously MTMR15 ) genes were associated with pathological complete response and residual invasive cancer in taxane/anthracycline‐treated patients. Conversely, PMS2 expression was associated with residual invasive cancer in treatments using anthracycline as a single agent. In HER2‐positive tumors, TOP2A was associated with patient response to anthracyclines but not to taxane/anthracycline regimens. In genes expressed in a bimodal fashion, RECQL4 was significantly associated with clinical outcome. In vitro studies showed that defects in RECQL4 impair homologous recombination, sensitizing BC cells to DNA‐damaging agents. Abstract : DNA repair pathways can enable tumor cells to survive DNA damage induced by chemotherapy and thus provide prognostic and/or predictive value. In this study, the authors sought to assess the differential expression, bimodal distribution, and prognostic and predictive role of DNA repair genes in individual breast cancer molecular subtypes including estrogen receptor‐positive/ HER2‐negative, estrogen receptor‐negative/HER2‐negative, and HER2‐positive cancers. The predictive value of DNA repair gene expression was assessed in breast cancer patients treated with neoadjuvant taxane/anthracycline‐ or anthracycline‐containing regimens, and gene set analyses were performed by grouping DNA repair genes according to biological pathways. Abstract : 摘要 DNA 修复通路可使肿瘤细胞幸免于化疗所引起的 DNA 损害，因而具有重要的预后和/或预测价值。我们在未经治疗的乳腺癌 (BC) 患者 ( n = 684) 和接受过新辅助化疗方案包含紫杉烷/蒽环类 ( n = 294) 或蒽环类 ( n = 210) 的 BC 患者中评估了 145 种 DNA 修复基因的 Affymetrix 基因表达谱。我们分别评估了雌激素受体 (ER)‐阳性/HER2‐阴性、HER2‐阳性以及 ER‐阴性/HER2‐阴性乳腺癌亚组的 DNA 修复基因差异表达情况、双峰分布情况以及预后和预测价值。ER‐阴性肿瘤有 22 个基因一致性过表达，ER‐阳性肿瘤有 5 个基因过表达，但是 HER2 的状态并未导致基因表达的差异。在 ER‐阳性/HER2‐阴性肿瘤中，有九个基因（ BUB1、FANCI、MNAT1、PARP2、PCNA、POLQ、RPA3、TOP2A 和 UBE2V2 ）的表达提示预后不良，有 1 个基因 ( ATM ) 的表达提示预后良好。此外，特定基因的预后价值与增殖并不存在相互关联。有几个基因与化疗应答存在关联，而且该应答因 BC 亚型和化疗类型而异。在 ER‐阴性/HER2‐阴性肿瘤中， MSH2 、 MSH6 和 FAN1 基因（以前称作 MTMR15 ）的表达在接受紫杉烷/蒽环类治疗的患者中提示与病理完全缓解和残余侵袭性癌相关。相反， PMS2 的表达在接受蒽环类单剂治疗的患者中提示残余侵袭性癌。在 HER2‐阳性肿瘤中， TOP2A 的表达提示患者可对蒽环类产生应答，但对紫杉烷/蒽环类联合化疗方案无应答。在呈双峰表达的基因中， RECQL4 与临床预后存在显著关联。体外研究表明，RECQL4 的缺陷可影响同源重组，使得 BC 细胞更容易受到 DNA 损伤剂的破坏。 The Oncologist 2013;18:1063–1073